Healthcare-Associated Pneumonia Does Not Accurately Identify Potentially Resistant Pathogens: A Systematic Review and Meta-Analysis. (22nd November 2013) - Chalmers, James D.; Rother, Catriona; Salih, Waleed; Ewig, Santiago
Abstract : A systematic evaluation of studies into healthcare-associated pneumonia (HCAP) indicates this concept does not accurately identify resistant pathogens, with evidence of publication bias and poor study quality. Mortality in HCAP patients is primarily due to comorbidities and not resistant pathogens. Abstract: Background.  The 2005 American Thoracic Society/Infectious Diseases Society of America guidelines introduced a concept of healthcare-associated pneumonia (HCAP) to define patients at higher risk of antibiotic-resistant pathogens, thus requiring broad spectrum therapy. There has been no systematic evaluation of the ability of this definition to identify antibiotic-resistant pathogens. Methods.  We conducted a systematic review and meta-analysis of studies comparing the frequency of resistant pathogens (defined as methicillin-resistant Staphylococcus aureus, Enterobacteriaceae, and Pseudomonas aeruginosa ) in populations with HCAP compared with populations with community-acquired pneumonia (CAP). Predictive accuracy was evaluated using the area under the receiver operator characteristic curve (AUC). The frequencies of pathogens in each group were pooled using a random effects model. Results.  Twenty-four studies were included (n = 22 456). Overall study quality was poor. HCAP was associated with an increased risk of methicillin-resistant S. aureus (odds ratio [OR], 4.72; 95% confidence interval [CI], 3.69–6.04) enterobactericeae (OR, 2.11; 95% CI, 1.69–2.63), and P. aeruginosa (OR, 2.75; 95% CI, 2.04–3.72; all P < .0001), but these analyses were confounded by publication bias. The discriminatory ability of HCAP for resistant pathogens was low (AUC, 0.70; 95% CI, 0.69–0.71) and was lower in high-quality (AUC, 0.66; 95% CI, 0.62–0.70) and prospective studies (AUC, 0.64; 95% CI 0.62–0.66). After adjustment for age and comorbidities, mortality was not increased in HCAP (OR, 1.20; 95% CI, 0.85–1.70; P = .30). Conclusions.  The HCAP concept is based on predominantly low-quality evidence and does not accurately identify resistant pathogens. Mortality in HCAP does not appear to be due to a higher frequency of resistant pathogens.